Prophylactic mesh reinforcement after open aortic aneurysm repair: a prospective cohort study - Sguinzi, Raffaella; Lagger, Melissa; Chevalley, Théo; Gremaud, Benoît; Menth, Markus; Buhler, Leo; Adamina, Michel (Frontiers in Surgery, 2025)
ObjectivesPatients undergoing elective open abdominal aortic aneurysm (AAA) repair via midline laparotomy are at significantly increased risk—up to threefold—of developing incisional hernias (IHs) compared to those treated for aorto-iliac occlusive disease using the same approach. Recent vascular surgery guidelines recommend prophylactic mesh reinforcement (PMR) during abdominal wall closure to reduce IH incidence. This study aims at evaluating the effectiveness of retromuscular PMR in preventing IH after open AAA repair and to assess related postoperative complications.MethodsThis was a prospective cohort study including patients who underwent open AAA repair with retromuscular PMR at our institution. Data collection included patient demographics, operative details, and postoperative complications. Clinical examination, abdominal ultrasound, and quality of life (QoL) were routinely assessed to evaluate the presence of IH and patient-reported outcomes. The primary endpoint was the incidence of IH; secondary outcomes included fascial dehiscence, seromas, surgical site infections (SSI), hematomas, chronic pain, and mesh displacement. Descriptive statistics were used to report outcomes, and findings were compared with existing literature.ResultsA total of 21 patients were included between 2019 and 2024 with a median follow-up of 32 months. IH occurred in 4 (19%) patients: three developed hernias after a re-laparotomy performed postoperatively with mesh incision and re-closure, and one hernia was detected on ultrasound without clinical symptoms. No cases of fascial dehiscence, seroma, or surgical site infection were reported, and nor was chronic pain or mesh displacement. QoL was well-preserved, with minimal functional limitations and an average general health score of 80%.ConclusionsRetromuscular PMR may reduce the incidence of IH after open AAA repair. Re-laparotomy appears to be a risk factor for hernia development. Although these results support current guideline recommendations, further data with larger cohorts are needed to confirm these findings.Registration numberObservational study NCT06762561 (https://www.clinicaltrials.gov).